Successful weaning of a patient with severe COVID-19 pneumonia under prolonged midazolam sedation using morphine. Issue 6 (23rd June 2022) - Kunimasa, Kei; Ohashi, Yoshifumi; Okawa, Megumi; Iida, Hiroshi; Sonoda, Shunji; Hiuge, Yuki; Hachimine, Masaaki; Yamamura, Ai; Kawamura, Takahisa; Inoue, Takako; Tamiya, Motohiro; Kuhara, Hanako; et al.
Abstract: The coronavirus disease 2019 (COVID-19) pandemic continues to spread around the world. In April 2021, Japan experienced a fourth wave of COVID-19 infections, which led to the breakdown of the medical system. Osaka, Japan, was particularly affected, with many severe cases and the highest number of COVID-19-associated deaths in Japan. Herein, we present a patient with severe COVID-19 infection who received prolonged midazolam (MDZ) treatment since propofol was not available due to shortage of medical resources. Moreover, the duration of mechanical ventilation was extended due to the development of a pneumothorax. When MDZ tapering was initiated, tachypnea was observed, which resulted failure in ventilator weaning. However, the use of continuous morphine infusion led a successful weaning off the ventilator. We suggest that the administration of morphine may allow for a smoother weaning process for some patients with severe COVID-19 infection.